Model Pengaturan Kedaruratan Dan Pilihan Kedaruratan Indonesia Dalam Menghadapi Pandemi Covid-19 - Arsil, Fitra; Ayuni, Qurrata (UI Scholars Hub, 2023)
Indonesia own various of legal models uses to deal with emergencies. Two emergency arrangements in the 1945 Constitution are represented by the phrase